Jenis Tumbuhan Sumber Nektar Lebah Apis dorsata Fabr. Dari Desa Bumi Harapan Dan Desa Bukit Raya Kecamatan Sepaku Kalimantan Timur - Wibowo, Eko Putra; Syafrizal, Syafrizal; Susanto, Dwi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2016)
This research aims to find out what kind of plants that become the source of nectar for Apis dorsata Fabr. in two different villages, namely Bumi Harapan village and Bukit Raya village, in Sepaku Region, East Borneo, and also to identify the pollen morphology of the nectar found in those plants that contained in honey. Based on the identification results of the nectar found from both villages there are significantly different number in variety of plants between these two samples. In Bumi Harapan, 27 families and 64 species of plants were found as the source of nectar, with 7 dominant families